2016
DOI: 10.1097/md.0000000000003261
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Willingness on Community Health Centers as Gatekeepers and Associated Factors in Shenzhen, China

Abstract: The gate-keeping function of primary healthcare facilities has not been fully implemented in China. This study was aiming at assessing the willingness on community health centers (CHCs) as gatekeepers among a sample of patients and investigating the influencing factors.A cross-sectional survey was conducted in 2013. A total of 7761 patients aged 18 to 90 years from 8 CHCs in Shenzhen (China) were interviewed using a structured questionnaire. Descriptive and multivariable logistic regression analyses were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
5
18
2
Order By: Relevance
“…Compared with patients without gatekeeping restriction, patients with insurance policy who contacted CHCs first were more likely to choose CHCs first, visit more often regularly, and, equally satisfied with their care at CHCs. Overall, our findings were consistent with previous studies, which had shown that gatekeeping increased the use of primary care [ 27 , 29 31 ] and reduced the use of specialists and hospital care, [ 14 , 16 , 31 – 34 ] but without adverse impact on patient satisfaction and health outcomes [ 27 , 29 , 35 – 37 ] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with patients without gatekeeping restriction, patients with insurance policy who contacted CHCs first were more likely to choose CHCs first, visit more often regularly, and, equally satisfied with their care at CHCs. Overall, our findings were consistent with previous studies, which had shown that gatekeeping increased the use of primary care [ 27 , 29 31 ] and reduced the use of specialists and hospital care, [ 14 , 16 , 31 – 34 ] but without adverse impact on patient satisfaction and health outcomes [ 27 , 29 , 35 – 37 ] .…”
Section: Discussionsupporting
confidence: 92%
“…Since the Ministry of Health issued in 2006 a directive endorsing this policy, health administrations in many provinces, districts, and cities had launched various pilot schemes to implement it, mostly in combination with other reforming initiatives aimed at promoting essential medicines use, chronic disease management, health promotion, etc. [ 23 – 26 ] Our previous study showed that patients’ willingness for visiting CHCs is high [ 27 ] and another study indicated that patient satisfaction with the gatekeeper policy was low [ 28 ] , however, the effects of the gatekeeper policy in China and patient satisfaction with community health service between patients with and without gatekeeper policy were not evaluated or compared.…”
Section: Introductionmentioning
confidence: 99%
“…Community-based services were described by many as a source for follow-ups or refills of medication when needed, rather than first-contact care. Our finding is contrary to previous study findings (15,16) that 60%-70% of their respondents were willing to select community-based providers for first contact care. The inconsistency can be caused by several reasons, and amongst all, a selection bias is possible by their sampling patients attending community health services.…”
Section: Discussioncontrasting
confidence: 57%
“…However, it is difficult to evaluate properly patients’ acceptance of gatekeeper policy among the pilot population because they could not experience the policy deeply in a short time. Previous study showed that patients’ willingness for visiting CHCs is high [ 14 ] and another study indicated that patients’ satisfaction with the gatekeeper policy was low [ 15 ], however, these study were conducted among migrant workers and they experience the policy only for 15 years. In fact, people covered by GIS have experienced gatekeeper policy for a long time, and their attitude towards the policy would be suitable and available for the assessment of the gatekeeper policy in China.…”
Section: Introductionmentioning
confidence: 99%